2015
DOI: 10.1182/blood.v126.23.975.975
|View full text |Cite
|
Sign up to set email alerts
|

Heme Concentration As a Biomarker of Sickle Cell Disease Severity: Its Role in Steady-State and in Crisis Patients

Abstract: Background: Sickle cell disease (SCD) is a heredity group of anemia characterized by hemolysis, chronic inflammation, and vaso-occlusive/painful crisis. The heme is a product of erythrocytes' lyses and is increased in hemolytic diseases. Objectives: To investigate associations between hematological/biochemistry biomarkers and total plasma heme levels between SCD patients groups (in crisis and in steady-state) and healthy controls. To identify molecules related to hemolysis, inflammation, hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Heme consists of an iron ion centered in a large organic ring and is mainly found in hemoglobin, but also in a few other important hemoproteins, with varying functions all related to redox chemistry. Free heme is highly cytotoxic and deleterious to tissues via its pro-oxidative and pro-inflammatory properties, as it is capable of catalyzing free radical formation [33,34,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heme consists of an iron ion centered in a large organic ring and is mainly found in hemoglobin, but also in a few other important hemoproteins, with varying functions all related to redox chemistry. Free heme is highly cytotoxic and deleterious to tissues via its pro-oxidative and pro-inflammatory properties, as it is capable of catalyzing free radical formation [33,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Because we used plasma, which is a cell-free matrix, it is anticipated that there is a greater contribution from “free heme” to the measurement of heme abundance unless substantial hemolysis occurred. High concentration of free heme in plasma is a biomarker for sickle cell disease severity, in which increased levels of inflammatory biomarkers such as lactate dehydrogenase, bilirubin, high reticulocytes count, and lipids are detected [35]. Three forms of bilirubin as well as biliverdin were assessed in our samples and were also present in higher abundance in patients vs. controls, demonstrating a general disturbance in the heme degradation pathway, with the last step occurring in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma hemin levels were increased in SCD patients compared to the almost-undetectable levels in controls. Hemin is produced by the oxidation of heme [26], a molecule which was suggested to be a biomarker of disease severity in SCD [27]. It has also been shown that hemin causes oxidative damage to plasma lipoproteins, such as LDL and HDL [28].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, free heme accumulates in the system [ 35 ]. Elevated levels of free heme are associated with increased incidence of VOC [ 36 ]. Free heme stimulates the migration of leukocytes to the endothelial wall where they bind to P- and E-selectins and promote the production of reactive oxygen species (ROS) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%